If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2 + -2x + 3 = 0 Reorder the terms: 2 + 3 + 7x + -2x = 0 Combine like terms: 2 + 3 = 5 5 + 7x + -2x = 0 Combine like terms: 7x + -2x = 5x 5 + 5x = 0 Solving 5 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 5x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 5x = 0 + -5 5x = 0 + -5 Combine like terms: 0 + -5 = -5 5x = -5 Divide each side by '5'. x = -1 Simplifying x = -1
| -6x-x+6+5= | | 7x-1=2x(7+5) | | 8n-7n+6=6 | | 6(c-4)+4=3+c-23 | | 6x/4=2x | | 18x+4y=112 | | 3(2z-2)=5(z+4) | | 3x+7=8+9x | | -7(x+9)-(8x-3)=6 | | 8.64x-9=2x*45 | | 3y-6+y+32=7y+30-5y | | 25+f=7 | | 5x+4y=-40 | | 16x^2-16x=48x^2+3 | | 3(t-6)+2=4(t+2)-21 | | 14/49= | | 41x^2-41x=-15x^2+7 | | b+2=2b | | 25=X-[[(P)14](.1)] | | 8-2n=4(5-n)-22 | | 25=X-[(P)14(.1)] | | -6x+5y=28 | | 25=X-(P)14(.1) | | 5(5n-3)= | | y-.5=.75 | | 3f+15=13+5f | | -14m-11=95 | | x(2-1)=2x+6x | | 4(n+6)=44 | | 1.4P(1.4)= | | 2a+5=6a+1 | | 4(7d+7)= |